Mental Health Interventions: Reflections on a Radio Program as Alternative for Stigma Reduction and Social Integration - Marino, María Inés; Adogba, Oluwabusola; Tilli, Nicolas (Frontiers in Communication, 2020)
Under the umbrella of Social Identity Theory and Goffman’s notion of stigma, this paper reviews research on stigma in connection with social perceptions of individuals with mental health problems and the role of the media in building those perceptions. The study specifically examined three aspects: (1) social stigma of individuals with mental health problems; (2) media as an alternative intervention for individuals with mental health problems, and (3) alternative interventions for stigma reduction and social integration. Based on data collected via testimonies from an in-hospital radio show, from hospitalized patients with mental health problems, and from the audience, the study was designed to address the question of how mass media could act as an alternative mental health intervention to help reduce stigma and promote social integration.